ANALYSIS OF TRENDS OF HYPERTENSIONS RELATING TO THE LEAVES AND CALCULATIONS IN BLOOD IN EMPLOYEE AND RECOVERY: CASE STUDY IN PLACE OF FINAL DISPOSAL (FD) MEDAN - MARELAN. - Saputri, Muharni; Harahap, Urip; Muchlisyam, Muchlisyam (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The aim of this study was to determine the relationship between lead and calcium to hypertension. Methods: This study uses causal comparative cross-sectional study, which subjects of study as many as 31 people consisting of 10 people in Group I (employees of final disposal [FD]), 17 people in Group II (scavengers who move in FD), and 4 people in Group III (control). Confounding variables in this study are the working period, age, and body mass index. Determining calcium content performed acetylene flame atomic absorption spectrophotometry-air while the lead is done by atomic absorption spectrophotometry graphite furnace method. Results: The results of the study showed differences of concentration lead of each group. In Group II on day 30 it contained a lead level of 29.9141 Î¼g/DL. This level has exceeded the threshold set by the WHO. Statistical test results using Rank Spearman correlation showed no relationship between lead and calcium to hypertension, the p value of each group was 0.187, 0.819, and 1.00. Conclusion: The results of this study can be concluded that the lead and calcium does not affect blood pressure on employees and scavengers in the FD Medan-Marelan.